Level of Satisfaction in the Health Care Service at Barangay Gulod Quezon City: Basis for a Proposed Improvement Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Barangay Health Care Center is a community-based facility that offers first aid, child healthcare, and other basic services to Barangay residents. This research aims to determine thelevel of satisfaction with the health care service provided by Barangay Gulod Quezon City.The result shows the percentage distribution of the respondents. The Demographic profileTable 1 shows age 18-59 50% and 60 above 50% with a total of 100%, while Gender Table2 shows the total number percentages of male respondents (33%) and female respondents(67%). Reliability Table 3 shows a composite mean of non-senior 3.35 and senior 3.52, withboth verbal interpretations strongly agreeing. Tangibles Table 4 shows a composite mean ofnon-seniors 3.44 with verbal interpretation strongly agree, and seniors 2.68 with verbalinterpretation agree. Vaccines and Medicine Table 5 composite mean of non-senior 2.53with verbal interpretation agree and senior 2.8 with verbal interpretation agree, Priority LaneTable 6 shows a composite mean of non-senior 2.27 with verbal interpretation disagree andsenior 3.24 with verbal interpretation agree, Records Table 7 shows a composite mean non-senior 2.57 with verbal interpretation agree and senior with verbal interpretation 2.55 agree,Responsiveness Table 8 shows a composite mean non-senior 3 with verbal interpretationagree and senior 3.19 with verbal interpretation agree, Table 9 shows the significantdifference between the assessments of non-senior and senior respondents in terms of citedvariables. It reveals that the reliability, vaccine and medicine, records, and responsivenesshave no significant differences between the two groups; however, the tangibles and prioritylane are significant for both respondents. Table 10 shows the problem and solution of theresearcher’s administrator.The researchers recommended an improvement plan to address the concerns highlighted inthe study and improve the healthcare center's service quality. These include conductingregular patient feedback surveys to identify areas for improvement and measure the successof implemented improvements, investing in staff training, and upgrading technology toimprove the efficiency and effectiveness of operations.
Keywords: Business Administration